Investigating the Outcomes of an Asthma Educational Program and Useful Influence in Public Policy - Ghaleb Dailah, Hamad (Frontiers in Public Health, 2021)
The study was conducted to evaluate the effectiveness of an asthma educational program for asthma control, asthma self-management, asthma knowledge, and patient activation. The study analyzes different demographic variables with the purpose of investigating which asthma patients performed better than others. Based on these demographic characteristics, the study provides several recommendations for various stakeholders. The study is based on a positivist approach since its purpose is to investigate the consequences of an asthma educational program with a view to generalizing the results to a larger population. The study targets public and private hospitals which have applied the asthma educational program in collaboration with the Saudi Initiative for Asthma (SINA). Multiple questionnaires were deployed 263 valid responses were received from patients of public and private hospitals using online and offline data collection method. Several parametric and non-parametric tests were carried out in terms of data analysis. The results reveal that patients in the intervention group obtained high scores and were therefore more knowledgeable and able to control their asthma compared to the control group. Overall, patients in the intervention group performed better in terms of asthma control, asthma self-management and knowledge and awareness. There was a high level of patient activation in this group. In the context of demographic features, it was found that patients who are married and are undergraduate degree holders in employment scored high compared to patients who were young, single, post-graduate degree holders that were mainly self-employed. The results of this study can guide policy makers, SINA authorities, and hospitals as to which demographic category of asthma patients require immediate attention. The significance of asthma educational programmes has increased especially through social media platforms as the number of adult patients continues to increase day by day.